Middle Cranial Fossa Approach: The Incudomalleolar Joint as a Reliable Landmark - Hashmi, Syed Salman; Izquierdo, Juan Carlos; Emmett, Susan D.; Linder, Thomas Edwin (International Archives of Otorhinolaryngology, 2020)
Introduction The middle cranial fossa approach is performed by fewer neurotologists owing to a reduced number of indications. Consistent landmarks are mandatory to guide the surgeon in a narrow field.Objectives We have evaluated the incus and malleus head and the incudomalleal joint (IMJ) as a key landmark for identifying the superior semicircular canal (SSC) and to get oriented along the floor of the middle cranial fossa.Methods A combination of 20 temporal bone dissections and CT imaging were utilized to test and describe these landmarks.Results The blue line of the SSC is consistently identified along the prolongation of a virtual line through the IMJ and the angulation toward the root of zygoma. The mean distance from the zygoma toward the IMJ ranged from 1.60 to 1.90cm. Once the IMJ was identified, the blue line of the SSC was consistently found along the virtual line through the IMJ within 5 to 9mm.Conclusions The IMJ is a safe and consistent anatomical marker in the surgical approach to the middle cranial fossa floor. Opening the tegmen 1.5 to 2cm medial to the root of the zygoma and identifying the joint allows to trace a virtual line toward the SSC within 5 to 9mm. Knowledge of the close relationship between the direction of the IMJ and the superior canal can be used in all transtemporal approaches, thus orienting the surgeon in a rather narrow field with limited retraction of the dura and brain.
Keywords: middle cranial fossa surgery; transtemporal-supralabyrinthine approach; superior semicircular dehiscence; arcuate eminence